The uses and abuses of the coherence – correspondence distinction - Polonioli, Andrea (Frontiers in Psychology, 2015)
Kenneth Hammond introduced a distinction between coherence and correspondence criteria of rationality as a tool in the study of judgment and decision-making. This distinction has been widely used in the field. Yet, as this paper seeks to show, the relevant notions of coherence and correspondence have been progressively considered to be too narrow and have undergone non-trivial conceptual changes since their original introduction. I try to show, first, that the proliferation of conceptualizations of coherence and correspondence has created confusion in the literature and that appealing to such notions has not helped to elucidate discussions over the nature of rational judgment and decision-making. Nevertheless, I also argue for a reframing of the debate. In fact, what seems to underlie several contemporary appeals to the notions of coherence and correspondence is best explained in terms of a contrast between what I call here rule-based and goal-based rationality. Whilst these categories do need further refinement, they do seem to be useful in organizing and understanding research on rational judgment and decision-making.